(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Introduction: The plant Combretum hypopilinum has many medicinal uses in Africa. Infusion of fresh or dry leaves are commonly taken as cholagogic, diuretic, and purgative and also to treat gastrointestinal disorders, including diarrhoea, dysentery, and stomach aches Objective: To carry out phytochemical and antidiarrheal studies on the methanol stembark extract of C. hypopilinum. Methods: The C. hypopilinum stembark (1kg) were extracted with methanol using cold maceration method for 9 days. The solvent was removed by rotary evaporator and the extract was partitioned with n-hexane, chloroform and ethyl acetate to give the n-hexane, chloroform, and ethyl acetate fractions respectively. The extract was subjected to preliminary phytochemical screening, acute toxicity study and antidiarrheal activity using animal models. Result: The following metabolites: carbohydrates, alkaloids, phenol, steroids, terpenes, saponins, flavonoids and tannins were revealed when the phytochemical screening of the plant extract was carried out. The oral median lethal dose (LD50) of crude extract in mice and rats was estimated to be above 5000 mg/kg. The antidiarrheal activity carried out at dose 150, 300 and 600 mg/bw i.p. using castor oil induced diarrheal, gastric-transit time and anti-enteropooling tests in mice and rats. The extract significantly (P<0.05) inhibited diarrheal in mice and rats with highest protection/ inhibition of 93.1% and 87.9% at doses of 600 and 300 mg/kg (dose dependently) which compared with atropine sulphate (86.2%) respectively, in the castor-oil induced diarrheal test in mice. The extract also significantly (P<0.05) inhibited diarrheal in charcoal meal test with the highest % protection of 24.38% at dose 600 mg/kg and compared with loperamide (28.80%). The anti-enteropooling test in rats showed 68% inhibition of diarrheal as compared to atropine sulphate with 78% inhibition. Conclusion: The results indicated that the methanol stembark extract of Combretum hypopilinum possesses significant dose dependant antidiarrheal activity (p<0.05) in all the antidiarrheal tests. Thus, the traditional use of the plant for the treatment of diarrheal is highly justified in this study.